Hepatitis E Virus: Isolation, Propagation, and Quantification. Issue 1 (18th January 2023) - Lin, Shaoli; Yang, Liping; Zhang, Yan‐Jin
Abstract: Hepatitis E virus (HEV) predominantly causes acute liver disease in humans and is transmitted via the fecal‐oral route. HEV infection in pregnant women can result in grave consequences, with up to 30% fatality. The HEV strains infecting humans mainly belong to four genotypes. Genotypes 1 and 2 are restricted to human infection, while genotypes 3 and 4 are zoonotic. HEV genotype 3 (HEV‐3) can cause both acute and chronic liver disease. Several cell lines (mainly hepatocytes) have been developed for HEV propagation and biological study. However, HEV production in these cell lines is suboptimal and inefficient. Here, we present methods for the isolation, propagation, and quantification of HEV. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Isolation and propagation of hepatitis E virus in cultured cells from clinical HEV specimens Support Protocol 1 : Quantification of HEV RNA by RT‐qPCR Basic Protocol 2 : Recovery of HEV from infectious cDNA clones and purification of the virus Support Protocol 2 : Quantification of HEV live particles by infectivity assay